Science and engineering practices in the content of Greek middle school physics textbooks about forces and motion - Margarita Papakonstantinou; Michael Skoumios (OmniaScience, 2021)
It has been argued that students' understanding of science ideas and concepts is based on their engagement in science and engineering practices. However, research studying science and engineering practices engaging in the content of school science textbooks is particularly limited. The aim of the present study is to develop a framework and investigate (through it) the level at which science and engineering practices engage in the content of Greek middle school Physics textbooks about forces and motion. The analysis was carried out on a total of 61 reports and activities on forces and motion that are included in school textbooks (student's book and lab workbook) used for teaching Physics to 13-year-old middle school students in Greece. Reports and activities were analyzed using content analysis. An assessment rubric called "Science and Engineering Practices Analytic Rubric" (SEPAR), which evaluates the level at which science and engineering practices engage in the above reports and activities, was used throughout the analysis. The analysis demonstrated the low level at which science and engineering practices engage in the analyzed content of these school textbooks. The SEPAR can be used for analyzing science instructional material. The results mean that no opportunities are provided to the students through the content of these school textbooks so that the students could use science and engineering practices and become familiar with them in order to better understand ideas and concepts about forces and motion.